Creation of novel training programmes mapped to the Joint Royal Colleges of Physicians Training Board Internal Medicine stage 1 curriculum. (2019) - McNulty, Marie; Carty, Elizabeth; Chakravorty, Indranil; Lisk, Clifford; Short, Nadia; Szram, Jo; Bryant, Catherine; Ball, Karen Le; Deaner, Andrew; Birns, Jonathan
No abstract available